Emprego do glicerol como fonte de carbono na produção fermentativa de 2,3-Butanodiol por Enterobacter aerogenes ATCC 13048 - Girardi, Viviane (My University, 2015)
In this work, the use of glycerol as carbon source for cell growth and 2,3-butanediol/acetoin production in the in cultivation of Enterobacter aerogenes ATTT 13048 was studied. The influence of initial substrate concentration (S0) and oxygen transfer rate (OTR) was assessed in batch-mode experiments. Initially, cultivations with S0 of approximately 20 to 180 g/L, impeller speed of 500 rpm and specific air flow rate of 0.50 volume of air per volume of medium per minute (vvm), corresponding to characteristic OTR values between 10 and 13 mmol/L/h approximately, were performed. In the sequence, runs with S0 in the range 40 to 180 g/L, with varying impeller speed (650 to 750 rpm) and specific air rate (0.50 to 0.87 vvm) were carried out to maintain the dissolved oxygen concentration close to 30% of saturation as long as possible during the process. Characteristic OTR values for the conditions with the upper-limit impeller speed (750 rpm) and specific air flow rate (0.87 vvm) were about 34 and 24 mmol/L/h for the lowest and highest glycerol concentrations, respectively. In batch mode, for any OTR evaluated, S0 values up to 60 g/L did not result in growth inhibition of E. aerogenes, with maximum specific growth rates (μX,m) of 0.70 and 0.73 h-1 being measured for low and high OTR, respectively. On the other hand, an S0 of about 180 g/L led to a strong cell growth inhibition, especially under low OTR condition, and glycerol consumption was incomplete. In the group of runs performed with low OTR, the largest final 2,3-butanediol/acetoin final concentration (63.6 g/L) was achieved with a measured S0 of 146.4 g/L, but the highest yield was attained with S0 = 92.7 g/L. In the cultivations under high OTR, the maximum final product concentration (46.8 g/L) was obtained with S0 = 92.7 g/L, whereas the maximum yield of 70% was achieved with S0 = 102.5 g/L. Increasing OTR values favored productivity and cell yield but, however, resulted in decreasing conversion of glycerol to products. Afterwards, two fed-batch cultivations were done to avoid the strong inhibition due to high glycerol concentrations, and to allow that elevated concentrations of 2,3-butanediol/acetoin could be achieved. The first fed-batch run was carried out at the high-OTR conditions previously defined and the second one with impeller speed of 750 rpm and specific air flow rate of 0.50 vvm. The mass of glycerol employed corresponded to that needed to have an S0 of 240 g/L in batch-mode. With high OTR, a final product concentration of 90.4 g/L was quantified after 56 h of process, that means a yield of 83.2% and a productivity of 1.61 g/L/h,. In the experiment with 750 rpm and 0.50 vvm, 102.6 g/L of products were obtained after 74 h, with a yield of 94.7% and a productivity of 1.37 g/L/h. During the final hours of the fed-batch cultivations, increasing oxygen concentrations, decreasing oxygen uptake rate and incomplete glycerol consumption were observed, these data indicating the occurrence of inhibition of the bacterium respiratory activity by the high product concentrations which were present in the medium. The results allow concluding that glycerol is an adequate substrate for the production of 2,3-butanediol/acetoin by E. aerogenes.
Neste trabalho, estudou-se o uso de glicerol como fonte de carbono para o crescimento celular e a produção de 2,3-butanodiol/acetoína em cultivo de Enterobacter aerogenes ATCC 13048. A influência da concentração inicial do substrato (S0) e da velocidade de transferência de oxigênio (OTR) foi avaliada em ensaios em regime descontínuo. Inicialmente, foram realizados cultivos com S0 na faixa aproximada de 20 a 180 g/L, frequência dos agitadores de 500 rpm e fluxo específico de ar de 0,50 vvm, correspondendo a uma OTR característica entre 10 e 13 mmol/L/h, aproximadamente. Na sequência, foram conduzidos ensaios com S0 na faixa de 40 a 180 g/L, com variações da frequência dos agitadores (650 a 750 rpm) e do fluxo específico de ar (0,50 a 0,87 vvm), a fim de manter a concentração de oxigênio dissolvido próxima a 30% da saturação pelo mais longo período possível durante o processo. Os valores de OTR característica para as condições de maiores frequência de agitadores (750 rpm) e fluxo específico de ar (0,87 vvm), com a mais alta e a mais baixa concentrações de glicerol, foram de cerca de 34 e 24 mmol/L/h, respectivamente. Em regime descontínuo, S0 de até 60 g/L não provocou inibição do crescimento de E. aerogenes, independentemente da OTR utilizada, sendo obtidos valores de máxima velocidade específica de crescimento (μXm) de 0,70 e 0,73 h-1, respectivamente para baixa e alta OTR. Por outro lado, S0 da ordem de 180 g/L provocou forte inibição no crescimento celular, especialmente sob baixa OTR, não havendo consumo completo do glicerol. No grupo dos ensaios com baixa OTR, maior concentração final de 2,3-butanodiol/acetoína (63,6 g/L) foi obtida com S0 quantificada de 146,4 g/L, mas o mais alto rendimento (91,8 %) foi alcançado com S0 = 92,7 g/L. Nos cultivos com alta OTR, a máxima concentração de produtos de 46,8 g/L foi atingida com S0 de 183,9 g/L, enquanto o rendimento máximo de 70% foi alcançado com S0 = 102,5 g/L. O incremento de OTR favoreceu a produtividade e o rendimento em células, mas prejudicou a conversão de glicerol em produtos. Em seguida, foram realizados dois cultivos em regime descontínuo alimentado, a fim de evitar-se a inibição provocada por altas concentrações de glicerol e permitir que elevadas concentrações de 2,3-butanodiol/acetoína fossem atingidas. O primeiro ensaio foi realizado sob as condições de alta OTR definidas e o ensaio seguinte sob frequência de agitadores de 750 rpm e fluxo específico de ar de 0,50 vvm. A massa de glicerol empregada correspondeu à que seria necessária para ter-se um S0 de 240 g/L em batelada. No cultivo com alta OTR, foi atingida concentração de produtos de 90,4 g/L após 56 h, correspondendo a um rendimento de 83,2% e a uma produtividade de 1,61 g/L/h. No ensaio com 750 rpm e 0,50 vvm, foram obtidos 102,6 g/L de produtos em 74 de processo, com rendimento de 94,7% e produtividade de 1,37 g/L/h. Nos tempos finais dos cultivos alimentados, foi observado aumento da concentração de oxigênio no meio, redução da demanda de oxigênio e consumo incompleto do glicerol, dados que indicam a ocorrência de inibição da atividade respiratória da bactéria pelas altas concentrações de produtos presentes no meio. Os resultados permitem concluir que o glicerol é um substrato adequado para a produção de 2,3-butanodiol/acetoína por E. aerogenes.
Keywords: Biocombustíveis; Bactérias; Fermentação; Dióxido de carbono; Biomass energy; Bacteria; Fermentation; Carbon dioxide